Micronutrient needs in critically Ill children undergoing continuous renal replacement therapy and protein requirements in acute kidney injury patients - Demet Demirkol; Gerard Cortina; Akash Deep (Journal of Pediatric Critical Care)
Nutrition is one of the cornerstones in the treatment and support of critically ill patients. Nutritional support includes the provision of calories, protein, electrolytes, vitamins, and trace elements through enteral or parenteral routes. Acute kidney injury (AKI) is a common problem in critically ill patients and can lead to severe consequences, impacting metabolism and nutritional status significantly. Furthermore, regardless of the modality used, renal replacement therapy (RRT) has profound effects on metabolism. Evidence on nutritional support during continuous renal replacement therapy (CRRT) is limited, and there are no established clinical guidelines for nutritional adaptations during CRRT in critically ill patients. This review outlines some essential principles for providing micronutrient support in critically ill patients undergoing CRRT and protein requirements in AKI patients.